2015
DOI: 10.1111/1751-7915.12258
|View full text |Cite
|
Sign up to set email alerts
|

ExploringComQXPAquorum‐sensing diversity and biocontrol potential ofBacillusspp. isolates from tomato rhizoplane

Abstract: Bacillus subtilis is a widespread and diverse bacterium t exhibits a remarkable intraspecific diversity of the ComQXPA quorum-sensing (QS) system. This manifests in the existence of distinct communication groups (pherotypes) that can efficiently communicate within a group, but not between groups. Similar QS diversity was also found in other bacterial species, and its ecological and evolutionary meaning is still being explored. Here we further address the ComQXPA QS diversity among isolates from the tomato rhiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 75 publications
0
42
0
Order By: Relevance
“…Similarly, Bais et al (99) suggested that biofilm formation and the production of the lipopeptide compound surfactin by B. subtilis on Arabidopsis roots is essential for the plant protection activity of this organism against Pseudomonas syringae. Recently, surfactin production by Bacillus biofilms was directly imaged on plant roots by matrixassisted laser desorption/ionization mass spectrometry imaging (MALDI MSI) (100) and showed that B. subtilis strains that originate from the same plant root can dramatically differ in surfactin production, but less so in their ability to form biofilms (101). However, biofilm strength and thickness depends also on the composition of extracellular matrix components and these change in relation to available nutrients (102).…”
Section: Bacillaceae As Plant-beneficial Rhizobacteriamentioning
confidence: 99%
“…Similarly, Bais et al (99) suggested that biofilm formation and the production of the lipopeptide compound surfactin by B. subtilis on Arabidopsis roots is essential for the plant protection activity of this organism against Pseudomonas syringae. Recently, surfactin production by Bacillus biofilms was directly imaged on plant roots by matrixassisted laser desorption/ionization mass spectrometry imaging (MALDI MSI) (100) and showed that B. subtilis strains that originate from the same plant root can dramatically differ in surfactin production, but less so in their ability to form biofilms (101). However, biofilm strength and thickness depends also on the composition of extracellular matrix components and these change in relation to available nutrients (102).…”
Section: Bacillaceae As Plant-beneficial Rhizobacteriamentioning
confidence: 99%
“…Several isolates of Bacillus , especially Bacillus subtilis directly affect plant growth promotion, by the mechanisms such as acting as nitrogen fixers, as well as producers of indol butyric acid (IBA) (Araujo, Henning, & Hungria, ), indol acetic acid (IAA), and siderophores (Puente, Bashan, Li, & Lebsky, ), in addition to biocontrol activity (Ali, Charles, & Glick, ; Hanif et al., ; Oslizlo et al., ) and activities of protein expression relevant to the pharmaceutical and industrial sector (Guan et al., ). Bacillus subtilis has such varied functional capacities, which suggests that it has a versatile potential to be used as a plant growth promoter.…”
Section: Introductionmentioning
confidence: 99%
“…Integration of P epsA - gfp reporter fusion into different strains was performed by transformation with YC164 genomic DNA (41) (Table 1). Integration of srfA::Tn917 (mls) mutation into different strains was performed by transformation with BM1044 genomic DNA (74) (Table 1). Strains with P tapA - yfp reporter fusion were constructed by transformation with BM1115 genomic DNA (75).…”
Section: Methodsmentioning
confidence: 99%